Optimised sensor selection for control and fault tolerance of electromagnetic suspension systems: A robust loop shaping approach - Michail, Konstantinos; Zolotas, Argyrios C.; Goodall, Roger M. (My University, 2014)
This paper presents a systematic design framework for selecting the sensors in an optimised manner, simultaneously satisfying a set of given complex system control requirements, i.e. optimum and robust performance as well as fault tolerant control for high integrity systems. It is worth noting that optimum sensor selection in control system design is often a non-trivial task. Among all candidate sensor sets, the algorithm explores and separately optimises system performance with all the feasible sensor sets in order to identify fallback options under single or multiple sensor faults. The proposed approach combines modern robust control design, fault tolerant control, multiobjective optimisation and Monte Carlo techniques. Without loss of generality, it's efficacy is tested on an electromagnetic suspension system via appropriate realistic simulations.
Keywords: Optimised sensor selection; Robust control; Fault tolerant control; Magnetic levitation; Multiobjective optimisation; Electromagnetic suspension